Understanding China's energy strategy and its sustained economic growth: present and future - Dan Shi (China Finance and Economic Review, 2015)
Heavy investment on energy resources is one of the reasons for the rapid economic growth we have witnessed in China since 2000. Excessive energy consumption growth strengthens China's coal-dominated energy structure. Meanwhile, the supply of energy has been fully converted to net imports, weakening favorable factors for economic growth and increasing the risk of energy security. The nationalization level for the energy sector is much higher than for other industries. But even for stateowned enterprises, there is a huge gap in enterprise efficiency between different production processes. With a changing domestic and international energy market environment, China's energy industry should switch from the speed-oriented model in the past and adjust obsolete mechanisms and policies.we must first focus more on developing the service industry and optimizing the structure of the manufacturing industry.Second, the government must use fewer short-term economic interventions.Third, we should strengthen external regulations on energy monopolies. Fourth, we should attach great importance to energy security.
Keywords: 330; Energy supply and demand; Energy security; Energy efficiency; Energy policy